High Mobility Ge pMOSFETs with ZrO2 Dielectric: Impacts of Post Annealing - Huan Liu (Nanoscale Research Letters, 2019)
Abstract This paper investigates the impacts of post metal annealing (PMA) and post deposition annealing (PDA) on the electrical performance of Ge p-type metal-oxide-semiconductor field-effect transistors (pMOSFETs) with ZrO2 dielectric. For the transistors without PDA, on-state current (I ON), subthreshold swing (SS), and capacitance equivalent thickness (CET) characteristics are improved with PMA temperature increasing from 350 to 500 °C. Crystallization of ZrO2 dielectric at the higher PMA temperature contributes to the increase of the permittivity of ZrO2 and the decrease of the density of interface states (D it), resulting in a reduced CET and high effective hole mobility (μ eff). It is demonstrated that Ge pMOSFETs with a PDA treatment at 400 °C have a lower CET and a steeper SS but a lower μ eff compared to devices without PDA.